THEORETICAL ANALYSIS OF THE EFFECTS OF COUNTERIONS ON THE SUPRAMOLECULAR ARRANGEMENT OF SULFAMETHOXAZOLE (CIPEEX, 2022)
SULFAMETHOXAZOLE (SMZ) IS A SULFONAMIDE THAT ACTS BY COMPETITIVELY INHIBITING THE FORMATION OF FOLATE FROM P-AMINOBENZOIC ACID (PABA). IN A DRUG DEVELOPMENT PROCESS, SALT FORMATION IS A STRATEGY TO MODULATE ITS PHARMACOKINETIC AND PHYSICOCHEMICAL PROPERTIES, SUCH AS: AQUEOUS SOLUBILITY, DISSOLUTION, PURITY, STABILITY AND TOXICITY. THIS WORK AIMS TO INVESTIGATE THE EFFECT OF COUNTERIONS (SODIUM, BROMINE AND CHLORINE ATOMS) ON THE SUPRAMOLECULAR ARRANGEMENT OF SULFAMETHOXAZOLE BY THE DENSITY FUNCTIONAL THEORY (DFT).&NBSP; SULFAMETHOXAZOLE BELONGS TO THE CLASS OF SULFONAMIDES AND ITS POLYMORPHS INCLUDE DIFFERENT COUNTERIONS SUCH AS SODIUM (NA+), BROMINE (BR-) AND CHLORINE (CL-). THE SULFAMETHOXAZOLE SALTS ARE SMZNA, SMZBR AND SMZCL. THESE SALTS CRYSTALLIZED IN A MONOCLINIC SOLID STATE ENVIRONMENT - SMZNA (C10H11N3O3S) NA+ IN SPACE GROUP 21/C, SMZCL (C10H11N3O3S)CL- - IN CC AND SMZBR (C10H11N3O3S) BR- IN C2/C . NATURAL BONDING ORBITALS SHOWED THAT THE HYPERCONJUGATIONS BETWEEN THE DONOR AND ACCEPTOR ORBITALS SUPPORT THE STABILITY OF INTERACTIONS BETWEEN IONS FOR THE FORMATION OF SALT CRYSTALS. THE PHYSICOCHEMICAL PROPERTIES AND MOLECULAR MODELING OF SMZ SALTS (NA +, CL- AND BR-) ARE THE BASIS FOR NEW PHARMACEUTICAL DEVELOPMENT STAGES OF SMZ, SUCH AS FORMULATIONS, SOLUBILITY AND STABILITY.